2003
DOI: 10.1016/s0022-5223(03)00736-0
|View full text |Cite
|
Sign up to set email alerts
|

Does antegrade blood cardioplegia alone provide adequate myocardial protection in patients with left main stem disease?

Abstract: The combined route of intermittent blood cardioplegia allows better results in left main stem disease. Such data are confirmed even in risk subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…Indeed, myocardial protection is an art which depends largely on the surgeon's experience and skills [1,2]. There is no consensus on using an optimal method for the protection of myocardium during ischaemic arrest, although it has been debated since the beginning of open heart surgery [3]. In patients with severe coronary stenosis (>90%) there might be maldistribution of antegrade cardioplegic solution in the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, myocardial protection is an art which depends largely on the surgeon's experience and skills [1,2]. There is no consensus on using an optimal method for the protection of myocardium during ischaemic arrest, although it has been debated since the beginning of open heart surgery [3]. In patients with severe coronary stenosis (>90%) there might be maldistribution of antegrade cardioplegic solution in the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate myocardial protection results in reduced incidence of perioperative myocardial damage and preserves left ventricular function in the postoperative period 15,16 . It also reduces the incidence of postoperative atrial fibrillation and lowers the need for inotropes 16,17 . Presently, no non‐invasive methods have been established to visualize the distribution of cardioplegia in real time or direct delivery of cardioplegia intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 It also reduces the incidence of postoperative atrial fibrillation and lowers the need for inotropes. 16,17 Presently, no non-invasive methods have been established to We have demonstrated that the intraoperative visualization of cardioplegia distribution is possible using the NIR fluorescent dye ICG and existing NIR imaging technology. This method is appealing because it is safe, non-invasive, and can be used in real time.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac index (CI), indexed systemic vascular resistances, indexed pulmonary vascular resistances (PVRI), and pulmonary capillary wedge pressure (PCWP) were registered before anesthetic induction, 10 min following aortic declamping, at ITU arrival, and at 24 and 48 h postoperatively. Inodilators were started immediately after aortic cross‐clamp removal, always starting with enoximone at a dosage of 5 µg/kg/min (13). The need for continuing enoximone following CPB discontinuation was based on Swan–Ganz monitoring.…”
Section: Methodsmentioning
confidence: 99%